The Diagnostic Value of MicroRNA-499 in Acute Myocardial Infarction: A systematic review and meta-analysis: Diagnostic Value of MicroRNA-499 in Acute Myocardial Infarction - Zhang, Zhiyuan; Yan, Feifei; Dong, Zichao; Du, Hong (Journal of Medical Biochemistry, 2024)
Background: The objective of this study was to assess the diagnostic efficacy of MicroRNA-499 in cases of acute myocardial infarction.Methods: On May 6, 2023, four electronic databases PubMed, Embase, Web of Science, and Cochrane Library were searched with no time restriction. Quality assessment was conducted using QUADAS-2. Random-effects meta-analysis was employed to combine sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR). The evaluation of publication bias was conducted through the utilization of Deeks' asymmetry test on the funnel plot.Results: The studies that were included in the analysis, encompassing sample sizes ranging from 63 to 1155, exhibited a pooled sensitivity of 0.88 and a specificity of 0.97. The pooled positive likelihood ratio (PLR) was determined to be 29.78, while the negative likelihood ratio (NLR) was found to be 0.13. Furthermore, the pooled diagnostic odds ratio (DOR) was calculated to be 236.10. The area under the curve (AUC) was reported as 0.98.Conclusions: MicroRNA-499 exhibits high sensitivity and specificity for diagnosing Acute Myocardial Infarction, indicating its potential as a valuable diagnostic biomarker.
Keywords: MicroRNA-499; Acute Myocardial Infarction; Diagnostic Value; Meta-analysis